Roles of excess minority carrier recombination and chemisorbed O2 species at SiO2/Si interfaces in Si dry oxidation: Comparison between p-Si(001) and n-Si(001) surfaces - Tsuda, Yasutaka; Yoshigoe, Akitaka; Ogawa, Shuichi; Sakamoto, Tetsuya; Yamamoto, Yoshiki; Yamamoto, Yukio; Takakuwa, Yuji (The Journal of chemical physics, 2022)
This study provides experimental evidence for the following: (1) Excess minority carrier recombination at SiO2/Si interfaces is associated with O2 dissociative adsorption; (2) the x-ray induced enhancement of SiO2 growth is not caused by the band flattening resulting from the surface photovoltaic effect but by the electron–hole pair creation resulting from core level photoexcitation for the spillover of bulk Si electronic states toward the SiO2 layer; and (3) a metastable chemisorbed O2 species plays a decisive role in combining two types of the single- and double-step oxidation reaction loops. Based on experimental results, the unified Si oxidation reaction model mediated by point defect generation [S. Ogawa et al., Jpn. J. Appl. Phys., Part 1 59, SM0801 (2020)] is extended from the viewpoints of (a) the excess minority carrier recombination at the oxidation-induced vacancy site and (b) the trapping-mediated adsorption through the chemisorbed O2 species at the SiO2/Si interface.